Spearcons for Patient Monitoring: Laboratory Investigation Comparing Earcons and Spearcons. (August 2017) - Li, Simon Y. W.; Tang, Tsz-Lok; Hickling, Anna; Yau, Szeyuen; Brecknell, Birgit; Sanderson, Penelope M.
Objective: We compared the effectiveness of single-tone earcons versus spearcons in conveying information about two commonly monitored vital signs: oxygen saturation and heart rate. Background: The uninformative nature of many medical alarms—and clinicians' lack of response to alarms—is a widespread problem that can compromise patient safety. Auditory displays, such as earcons and spearcons (speech-based earcons), may help clinicians maintain awareness of patients' well-being and reduce their reliance on alarms. Earcons are short abstract sounds whose properties represent different types and levels of information, whereas spearcons are time-compressed spoken phrases that directly state their meaning. Listeners might identify patient vital signs more accurately with spearcons than with earcons. Method: In Experiment 1 we compared how accurately 40 nonclinician participants using either (a) single-tone earcons differentiated by timbre and tremolo or (b) Cantonese spearcons recorded using a female Cantonese voice could identify both oxygen saturation and heart rate levels. In Experiment 2 we tested the identification performance of six further nonclinician participants with spearcons recorded using a male Cantonese voice. Results: In Experiment 1, participants using spearcons identified both vital signs together more accurately than did participants using earcons. Participants using Cantonese spearcons also learned faster, completed trials faster, identified individual vital signs more accurately, and felt greater ease and more confident when identifying oxygen saturation levels. Experiment 2 verified the previous findings with male-voice Cantonese spearcons. Conclusion: Participants identified vital signs more accurately using spearcons than with the single-tone earcons. Application: Spearcons may be useful for patient monitoring in situations in which intermittently presented information is desirable.